A Sustainable Bioeconomy : The Green Industrial Revolution - Sillanpää, Mika; Ncibi, Chaker (Springer International Publishing : Imprint: Springer, 2017)
An authoritative and comprehensive volume of knowledge and green technologies wholly focused on the future of the bioeconomy. The authors present data, show opportunities, discuss R&D findings, analyze strategies, assess the wider economic impact, showcase achievements, criticize policies and propose solutions for the green revolution in biofuels, biochemicals and biomaterials' production and power generation. A fascinating range of case studies from the US, China and many European countries are used to inform readers about the impact of this field on society and how various technologies are currently being implemented. Additionally, the role of industry on this green industrial revolution is outlined with contributions from several major companies such as DuPont (US), UPM-Kymmene Oy (Finland), Anhui BBCA Biochemical Co (China).
Keywords: Chemistry.; Renewable energy resources.; Chemical engineering.; Renewable energy sources.; Alternate energy sources.; Green energy industries.; Environmental chemistry.; Sustainable development.; Environmental economics.; elektronické knihy; electronic books